Avaliação da aprendizagem na transformação social: uma análise das práticas avaliativas em uma escola, no município de Uruçuí – PI - Castro, Marta Lemos (2023)
The present study with a concentration area in management and teacher training in Basic Education, is linked to the line of research in educational and school management of the Graduate Program in Education at the State University of Maranhão (UEMA) and is constituted from the interest in knowing what are the conceptions of the manager, coordinator and teachers of the initial years of Elementary School, of a public school of Uruçui-PI, have on learning evaluation. It recognizes the importance of all types of assessment but focuses on the one that corroborates teaching-learning, bringing critical and conscientious reflections. For this, it sought to understand the most diverse conceptions that guide the pedagogical practice of these professionals in order to find mechanisms for improving the quality of learning assessment in accordance with the reality experienced in the school context. The research has as main objective to analyze the conceptions of the manager, coordinator and teachers, of a public school that offers the Initial Years of Fundamental Education, about the evaluation of learning. identifying possibilities and notes necessary for social transformation, with the purpose of contribute to knowledge through awareness-raising evaluative processes that promote quality learning assessment. For this, it has a theoretical and historical survey on the evaluation of learning. As a theoretical framework, it is drawn from the contributions of authors such as Hoffmann (2011; 2019), Luckesi (2009; 2011: 2014). Saul (2008; 2010; 2015; 2016), Freire (1976; 1997; 2014; 2018; 2019; 2021), Romão (1998; 2020), among others. It uses as methodology the field research defended by Gil (2008), from a qualitative approach conceptualized by Minayo (2007) and Teixeira (2013). As a data production technique, the semi-structured interview based on Minayo (2007). For data analysis and discussion, it relies on the principles of content analysis in Bardin (1979: 2016), with which we can trace the discussion of results into categories. The data produced indicate the importance of knowing what the conceptions of the manager, coordinator and teachers are of the researched school, and from them, to analyze, reflect and suggest new ways of perceiving the evaluation of learning. thus strengthening the debate on the researched theme. It also informs the relevance of a product that enables studies and guidance on social transformation from an emancipatory perspective through a notebook with guidelines, meeting the guidelines of the legislation